Cognitive Styles Vis-A-Vis Proficiency in Productive Skills - Tendero, Julieta (JPAIR Multidisciplinary Research, 2010)
This study was conducted to determine the relationship between the cognitive styles and the English proficiency (EP) scores in the productive skills of the Western Mindanao State University college students with other variables of age and area of specialization. To carry out its objective, the study employed the descriptive method, specifically the correlation technique. First, the respondents’ cognitive styles in information processing were determined through the use of the standardized Hemispheric Dominance Test (HDT). Then, the proficiency levels in the productive skills and global English were measured by the use of the Speaking Skill Test, the Writing Skill Test and the Cloze Test; all had been validated and reliability-tested. Lastly, the data were analyzed using mainly the Pearson r. Having a sample of 240 selected through purposive, stratified, and random sampling from the 5,096 students of the three colleges of Western Mindanao State University, Zamboanga City, results revealed that: that most of the students of the Colleges of Arts and Sciences, Engineering and Education of Western Mindanao State University were left-brained; that the students were “good” in speaking, “fair ” in writing but “poor” in global English; that there was no significant relationship between the cognitive styles and their EP scores in speaking, writing and global English tests; and that a significant relationship was shown between cognitive styles and EP scores in speaking, writing and global English when respondents were grouped according to age and area of specialization.